4D printed thermally activated self-healing and shape memory polycaprolactone-based polymers. (April 2018) - Invernizzi, Marta; Turri, Stefano; Levi, Marinella; Suriano, Raffaella
Graphical abstract: Highlights: Ureido-pyrimidinone (UPy) units are incorporated in a polycaprolactone (PCL). A PCL/UPy-based polymer is 4D printed by digital light projector (DLP) technology. Good shape memory and self-healing properties are shown by the 4D printed material. Mechanical properties of printed PCL/UPy samples are comparable to the neat PCL. Printed and repaired objects can act as soft actuators with enhanced durability. Abstract: The ability to change the shape of 3D printed objects as a function of time is known as 4D printing. Shape memory polymers with their shape-changing behavior are emerging as attractive materials to produce actuators for soft robotics. They can be transformed from one shape to another by a thermo-mechanical programming process. Self-repairing capabilities are also desirable for soft actuators to enhance their durability and mimic natural tissues. The possibility to produce 4D printed polymers with shape memory effect has proven but self-healing behavior was not attained so far in 4D printed shape memory objects. The focus of the present work is to demonstrate the capability of a newly developed material and of a customized low-cost 3D printer to produce 4D printed self-repairing objects. A 4D printed shape memory polymer with thermally induced healing abilities is first presented in this work and achieved by digital light projection (DLP) technology. Shape memory and self-healing functionalities are thermally triggered and obtained respectively using polycaprolactone (PCL) chains and 2-ureido-4[1 H ]-pyrimidinone (UPy) units co-crosslinked in this newly prepared material. Printed PCL/UPy-based objects show a stiffness similar to PCL-based ones, a higher elongation at break and a shape memory effect better than other printed PCL samples found in literature. The printability of shape memory objects is demonstrated with the printing of an opposing thumb, capable of being moved forward to the tip of a forefinger and then backward. Shape memory functionalities are still preserved after healing, making these printed actuators suitable for the production of components for human-machine interactions and soft robotics.